Saga - Vol 8 - Vaughan, Brian K. (Berkeley, CA : Image Comics, 2017)
When two soldiers from opposite sides of a never-ending galactic war fall in love, they risk everything to bring a fragile new life into a dangerous old universe.
Keywords: Families -- Comic books, strips, etc; Imaginary wars and battles -- Comic books, strips, etc; Military deserters -- Comic books, strips, etc; Science fiction comics; Graphic novels